Géotourisme et médiation scientifique dans l’offre touristique en montagne - Jonathan Bussard; Emmanuel Reynard (Revue de Géographie Alpine)
The spectacular landscapes of the site Swiss Alps Jungfrau-Aletsch (Bernese Alps), inscribed on the UNESCO World Heritage List since 2001, are recognised for their high scientific interest in the field of geomorphology. The heritage recognition of their geomorphological characteristics by various actors favours the development of geotourism, a form of tourism that aims to diversify the offer of tourist activities while raising visitors' awareness of the heritage value of the sites, through the implementation of interpretation facilities. This article proposes an analysis of the interpretation offers of the geomorphology in the region, evaluated and categorised on the basis of a multi-criteria grid in order to observe to what extent they achieve these two objectives. The 33 offers inventoried have very diverse characteristics, both in their form and in their content. Half of them succeed in demonstrating the scientific interest of the sites presented. In such cases, interpretation makes it possible to reveal their heritage dimension and to overcome the "mask of the picturesque" which tends to conceal the scientific interest of the sites behind their aesthetic characteristics. On the other hand, in some cases, the economic activation of the resources is not accompanied by the awareness of the heritage value, which excludes the offers concerned from the field of geotourism.